2017
DOI: 10.1007/s10802-017-0278-5
|View full text |Cite
|
Sign up to set email alerts
|

Do Overgeneral Autobiographical Memories Predict Increased Psychopathological Symptoms in Community Youth? A 3-Year Longitudinal Investigation

Abstract: Research suggests that an overgeneral autobiographical memory style (i.e., retrieval of general memories when instructed to retrieve a specific episodic memory) represents a vulnerability marker for depression. Although adolescence is a period of high risk for the emergence of depression, little research has investigated the associations among overgeneral memory, psychopathology, and risk factors longitudinally in a community sample in this age group. We, therefore, investigated overgeneral memory, psychopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 60 publications
8
33
0
Order By: Relevance
“…The relationship between positive memory specificity and depressive symptoms was dependent on exposure to stressful events as they occurred naturally over time. This conditional relationship is in line with findings in a recent longitudinal community study, which did not find an association between low memory specificity and subsequent depression; however, the study did not take the potential interaction with recent life events into account 41 . Importantly, we found that positive memory specificity was only associated with fewer negative self-cognitions during low mood and lower morning cortisol over time, and not at baseline.…”
Section: Insert Table About Heresupporting
confidence: 90%
See 1 more Smart Citation
“…The relationship between positive memory specificity and depressive symptoms was dependent on exposure to stressful events as they occurred naturally over time. This conditional relationship is in line with findings in a recent longitudinal community study, which did not find an association between low memory specificity and subsequent depression; however, the study did not take the potential interaction with recent life events into account 41 . Importantly, we found that positive memory specificity was only associated with fewer negative self-cognitions during low mood and lower morning cortisol over time, and not at baseline.…”
Section: Insert Table About Heresupporting
confidence: 90%
“…No statistical methods were used to pre-determine the sample size. However, our sample size is larger than those reported in previous publications 24,41,63 Autobiographical Memory Test 29 . All ambiguous / uncertain codings were discussed at a consensus meeting of trained researchers and a coding was agreed upon.…”
Section: Methodsmentioning
confidence: 71%
“…Our effect of positive memory specificity on depressive symptoms was dependent on exposure to stressful events as they occurred naturally over time. This conditional effect is in line with findings in a recent longitudinal community study, which did not find an association between low memory specificity and subsequent depression; however, the study did not take the potential interaction with recent life events into account 41 . Importantly, effects of positive memory specificity on negative self-cognitions during low mood and morning cortisol were only present over time, and the mechanisms involved are unknown.…”
supporting
confidence: 90%
“…We had expected that participants with more severe depressive symptoms would show lower specificity than participants with less‐severe symptoms; however, this was not the case. It may be that individual differences in posttraumatic stress and depressive symptoms are poorly associated with differences in specificity, and that compromised specificity is only evident when people with diagnoses of PTSD or depressive disorders are compared with control participants, or when this association is analyzed within at‐risk samples of participants such as those who show other cognitive vulnerabilities (Gutenbrunner, Salmon, & Jose, ; Raes, Hermans, Williams, & Eelen, ). It may be that in the studies sampled, there was insufficient variability between participants in their posttraumatic stress and depressive symptoms and as such it might not have been possible to adequately explore the association between these symptoms and differences in specificity.…”
Section: Discussionmentioning
confidence: 99%